Unusual and tunable negative linear compressibility in the metal–organic framework MFM-133(M)(M = Zr, Hf) - Yan, Yong; O'Connor, Alice E.; Kanthasamy, Gopikkaa; Atkinson, George; Allan, David R.; Blake, Alexander J.; Schröder, Martin (American Chemical Society, 2018)
High pressure single-crystal X-ray structural analyses of isostructural MFM-133(M) (M = Zr, Hf) of flu topology and incorporating the tetracarboxylate ligand TCHB4– [H4TCHB = 3,3',5,5'-tetrakis(4-carboxyphenyl)-2,2',4,4',6,6'-hexamethyl-1,1'-biphenyl] and {M6(μ-OH)8(OH)8(COO)8} clusters, confirm negative linear compressibility (NLC) behavior along the c axis. This occurs via a three-dimensional winerack NLC mechanism leading to distortion of the octahedral cage towards a more elongated polyhedron under static compression. Despite the isomorphous nature of these two structures, MFM-133(Hf) shows a higher degree of NLC than the Zr(IV) analogue. Thus, for the first time, we demonstrate here that the NLC property can be effectively tuned in a framework material by simply varying the inorganic component of the frameworks without changing the network topology and structure.